2011
DOI: 10.3892/mmr.2011.676
|View full text |Cite
|
Sign up to set email alerts
|

Combination of branched-chain amino acid and angiotensin‑converting enzyme inhibitor improves liver fibrosis progression in patients with cirrhosis

Abstract: Abstract. An effective therapeutic strategy for suppressing liver fibrosis should improve the overall prognosis of patients with chronic liver diseases. Although enormous efforts are ongoing to develop anti-fibrotic agents, no drugs have yet been approved as anti-fibrotic agents for humans. Insulin resistance (IR) is reportedly involved in the progression of liver fibrosis. The aim of the present study was to evaluate the effect of combination treatment with a clinically used branched-chain amino acid (BCAA) a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…A 48-month follow-up revealed that single treatment with ACEI did not exert inhibitory effects on hepatic fibrosis. 31 In a hepatitis C long-term treatment against cirrhosis trial, continuous ACEIs/ARBs use for 3.5 years did not retard the progression of hepatic fibrosis. 32 Several randomized controlled trials (RCTs) investigated the role of ACEI/ARBs in liver fibrosis with conflicting findings.…”
Section: Introductionmentioning
confidence: 99%
“…A 48-month follow-up revealed that single treatment with ACEI did not exert inhibitory effects on hepatic fibrosis. 31 In a hepatitis C long-term treatment against cirrhosis trial, continuous ACEIs/ARBs use for 3.5 years did not retard the progression of hepatic fibrosis. 32 Several randomized controlled trials (RCTs) investigated the role of ACEI/ARBs in liver fibrosis with conflicting findings.…”
Section: Introductionmentioning
confidence: 99%
“…The precise biological mechanisms underlying the protective effects of ACEIs or ARBs against cancer development is that the angiotensin I–VII levels increase during the inhibition of the ACE–angiotensin II–angiotensin II type 1 receptor (AT1R) axis, resulting in the activation of the Mas receptor and subsequent inhibition of cell proliferation and angiogenesis [ 27 , 28 ]. Moreover, ACEIs or ARBs have been reported to reduce liver fibrosis in human studies [ 29 , 30 ]. Further studies are warranted to determine whether these positive scientific findings can be used to extrapolate the efficacy of ACEIs or ARBs into clinical practice and translate this rationale into effective health intervention for high-risk populations [ 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, it may be difficult to really suppress the cumulative development of HCC with either single agent in clinical practice. Actually, we have shown that the combination treatment with ACE‐I and branched‐chain amino acids (BCAA), which are used for improvement of nutrition in patients with liver cirrhosis, exerted a marked inhibitory effect on rat hepatocarcinogenesis, whereas single treatment with ACE‐I or BCAA alone did not exert any inhibitory effect in clinical practice both in the cumulative recurrence of HCC and liver fibrosis development . Only the combination treatment with ACE‐I and BCAA induced a significant inhibition in clinical practice.…”
Section: Discussionmentioning
confidence: 99%